Anatomia foliar e análise de EDX de Costus spiralis (Jacq.) Roscoe de ambiente impactado e não impactado do litoral de São Paulo. - Calaboni, C. [UNESP]; Martins, M. B. G. [UNESP]; Rossi, M. L. (Fundação Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2013)
Several plants show morphological changes when exposed to environmental stress. We aimed to analyze comparative anatomy and EDX (energy dispersive x-ray detector) of Costus spiralis (Jacq.) Roscoe leaves from Jureia-Itatins Ecological Station (Peruibe, Sao Paulo), a preserved area, and Mogi River Valley (Cubatao, Sao Paulo) an affected area by pollution from the industrial complex of Cubatao. There were some significant differences in the leaves from the affected area, where they had a smaller abaxial hypoderm, larger size of adaxial hypoderm and larger central vascular core. There were damages in epicuticular wax deposition. The EDX analyses presented only differences in calcium and potassium concentration and presence of manganese in Cubatdo samples. Those leaves presented crystal deposition in the vascular core, probably because of the phosphogypsum residues from fertilizer industries.
Anatomical characterization of Costus spiralis (Jacq.) Roscoe leaves from impacted and non-impacted environments from the Sao Paulo coast
Keywords: anatomical characterization; Cubatao; Jureia-Itatins; Zingiberaceae